Posttreatment Downregulation of Type III Interferons in Patients with Acute Brucellosis. (19th July 2021) - Shokri, Mehran; Khonakdar, Oreinab Ghaffari; Mohammadnia-Afrouzi, Mousa; Sadeghi-Haddad-Zavareh, Mahmoud; Hasanpour, Amirhossein; Barary, Mohammad; Ebrahimpour, Soheil
Abstract : There is a limited number of clinical studies on interferon (IFN) levels in human brucellosis. The novel group of interferons, type III interferons, which consists of four IFN- λ (lambda) molecules called IFN- λ 1 or interleukin-29 (IL-29), IFN- λ 2 or IL-28A, IFN- λ 3 or IL-28B, and IFN- λ 4, is not fully known. This study is one of the first studies of IL-28A and IL-29 levels in brucellosis cases at the end of their treatment course. A total of 33 acute brucellosis patients were included in this study. We considered changes in the levels of IL-28A and IL-29 in cases with acute brucellosis before and after treatment with standard therapy that referred to the Ayatollah Rohani Hospital in Babol, northern Iran. Of 33 included patients, 22 (66.6%) were males, and 11 (33.4%) were females. The range of patients' age was 49.21 ± 17.70 years. Serum IL-29 and IL-28A (acute form: 56.4 ± 30.32 pg/mL and 48.73 ± 27.72 pg/mL, respectively, and posttreatment: 40.15 ± 20.30 pg/mL and 38.79 ± 22.66 pg/mL, respectively) levels were elevated significantly in acute brucellosis than after treatment (p < 0.05 ). These findings indicate that considering biomarker levels in brucellosis patients may indicate the chronicity of infection. In conclusion, we suggest that IL-29 and IL-28A levels may be valuable biomarkers for follow-up patients with brucellosis.